Effectiveness and Safety of Oral Azvudine for Elderly Hospitalized Patients With COVID‐19: A Multicenter, Retrospective, Real‐World Study - Ranran Sun; Haiyu Wang; Junyi Sun; Mengzhao Yang; Shixi Zhang; Xinjun Hu; Bo Yu; Zhan Song; Na Han; Hong Luo; Ming Cheng; Guangming Li; et al. (Advanced Science)
Abstract Azvudine is recommended as a priority treatment for patients with Coronavirus Disease 2019 (COVID‐19) during Omicron wave in China, but its efficacy and safety in elderly patients is unknown. In this multicenter, retrospective study, we identified 19763 elderly patients (aged over 60 years) with COVID‐19 from nine hospitals in Henan Province, China. The primary outcome is all‐cause death and the secondary outcome is composite disease progression. After propensity score matching, 4109 Azvudine recipients and 4109 matched controls is included, with average age of 75.15 years. Kaplan–Meier analysis reveales a notably survival and progression‐free benefit in Azvudine treatment. The Cox analysis shows that compared with controls, Azvudine recipients have a 33% lower risk of all‐cause death (95% confidence Interval (CI): 0.580–0.772, p < 0.001), but have no significant difference in composite disease progression (hazard ratio: 0.93, 95% CI: 0.833‐1.046, p = 0.234). Subgroup analysis suggested Azvudine have a stronger protective effect in patients concomitant with antibiotics. Three sensitive analyses confirm the robustness of the findings. The safety of Azvudine in elderly patients is acceptable. These findings indicate that Azvudine therapy can reduce the rate of all‐cause death in hospitalized elderly patients with COVID‐19, and without obvious adverse events.